Singaporean adolescents' perceptions of violence: Implications for practice. (July 2013) - Nair, Sudha; Osman, Mohammad Maliki
Culture, religion and ethnicity appear to impact how adolescents view their experiences of interpersonal violence. Despite the fact that these adolescents were third and fourth generation Singaporeans of Chinese, Indian and Malay descent, this qualitative study showed that while they did not condone the violence; their acceptance of it was largely governed by their interpretation of the scriptures, their ability to externalize control and responsibility to an external source like 'God' or 'fate', and the intergenerational transmission of culture in which they were socialized. A convenience sampling method was chosen to interview 52 adolescents who had grown up exposed to interpersonal violence. The study's objective was to determine whether culture, religion and ethnicity influenced their understanding of the perpetration of interpersonal violence. It answered the research question: What meanings do adolescents give to their life experiences in relation to growing up exposed to interpersonal violence? With increasing globalization and the cultural diversity in our societies, social workers must be ethnically and culturally sensitive to the worldviews of adolescents from differing backgrounds, if they are to engage them successfully. From a policy perspective, gender education which includes issues of equality and respect needs to be consciously developed in the school's curricula. Early outreach programmes are critical to identify these young victims of abuse before shame and loyalty issues in adolescence set in.